2019
DOI: 10.1186/s12883-019-1451-y
|View full text |Cite
|
Sign up to set email alerts
|

Social work support and unmet social needs in life after stroke: a cross-sectional exploratory study

Abstract: Background Stroke patients are often affected by long-term disabilities with needs concerning social issues. There is relatively little consideration of social recovery of patients and the support required to return to work, receive social benefits, participate in daily life activities, maintain contact with family and friends and to organize financial affairs. In our study we aimed to investigate if existing tools record social needs adequately. We analyzed the current provision of social support… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 55 publications
(60 reference statements)
0
16
0
1
Order By: Relevance
“…Similarly, a study conducted in Germany found that 54% of survivors reported they need more information about the cause of their stroke and prevention of recurrence. 20 In our study, 54% reported needs related to pain management (they have constant pain and nothing seems to ease it). On the other hand, a study conducted in England stated that only 39.5% of stroke survivors reported unmet needs regarding pain.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Similarly, a study conducted in Germany found that 54% of survivors reported they need more information about the cause of their stroke and prevention of recurrence. 20 In our study, 54% reported needs related to pain management (they have constant pain and nothing seems to ease it). On the other hand, a study conducted in England stated that only 39.5% of stroke survivors reported unmet needs regarding pain.…”
Section: Discussionmentioning
confidence: 56%
“…This finding was consistent with a study conducted in Germany by which the level of disability of stroke survivors was significantly associated with unmet psychosocial supportive care needs. 20 Physiotherapy utilisation was reported by 37.2% of the participants in this study. Similarly, a study which was conducted in West Africa stated that the physiotherapy utilisation of stroke survivors is low.…”
Section: Clinical Characteristicsmentioning
confidence: 61%
See 1 more Smart Citation
“…Stroke survivors report a wide range of needs which included: (i) cognitive, psychological and physical function needs; (ii) activity and participatory needs; and (iii) environmental needs, like support, safety and accessibility (Krishnan et al., 2017 ). There is, however, a growing evidence that multiple long‐term needs remain unmet poststroke (Lehnerer et al., 2019 ; McKevitt et al. 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of post stroke management with individual courses, impairments, and needs, impedes the development of overarching concepts [ 5 , 6 ]. Goals include, first, the best possible reduction of stroke-related impairments to alleviate the individual burden and enable social participation or return to work wherever possible.…”
Section: Introductionmentioning
confidence: 99%